Language Style in Horror Movies - Yulia Silpitri; Hamzah Hamzah (English Language and Literature, 2023)
The aim of this research is to compare the differences and similarities between The Conjuring 1 and The Conjuring 3 in the level of Field. This study was analyze using Halliday’s systemic functional linguistics theory. This study is a descriptive research. According to the study findings, both of Conjuring 1 and Conjuring 3 have four similarities and four differences in the level of Field. The findings lead to the conclusion that both of Conjuring 1 and Conjuring 3 are more similar than different and affects in how they produce utterances are influenced by word selection at the Field level, in context of situation.